Bee Systematics and Conservation - Eduardo A. B. Almeida; Margarita M. López-Uribe; Laurence Packer; Diego S. Porto; Gabriela P. Camacho (Sociobiology)
Diversity can be examined and interpreted from various perspectives, including species richness, genetic and phenotypic differences, variation in behaviors and natural history, and phylogenetic history. Centuries of taxonomic research have revealed approximately 21,000 bee species worldwide. These can be subdivided into a hierarchy of subgroups that reflects their evolutionary history, thanks to the increasingly more comprehensive phylogenetic hypotheses available. Advances in bee systematics have enhanced our understanding of how their diversity has evolved, including their origin in the Cretaceous, shifts in their geographical distribution, the evolution of social and parasitic behaviors, and changes in relationships between bees and the plants they visit throughout a 120-million-year shared evolutionary history. An important outcome of the enduring relationship with flowering plants is the vital role bees play in pollination in both natural and agricultural ecosystems. Habitat loss, climate change, and other anthropogenic environmental alterations have led to declines in bee populations, which have sparked concerns about bee conservation and highlighted the importance of understanding the complementary aspects of diversity, including the evolutionary and geographical components of this variation. The availability of increasingly reliable and comprehensive phylogenetic hypotheses has led to significant advancements, enabling assessments of the phylogenetic diversity of bee communities and predictions regarding their vulnerability to habitat change and their ecological functions. This review explores perspectives of documenting and interpreting bee diversity in a changing world and summarizes the current bee classification while discussing the phylogenetic advances in contemporary research.